Projeto e construção de um veículo terrestre autônomo para uso na agricultura - Godoy, Edson (2018)
Mobile robots have been studied over the years for most varied application areas, from home appliances to aerospace applications as Mars Rover. Because of their simplicity, has been used for several types of studies as basis for control strategies and computer vision in a wide range of areas. In this dissertation was approached the mechanical construction of a mobile robot for application in the agricultural engineering, with its own application characteristics. At the end of the work, a structure with a variable width, robust and low cost was developed, allowing its use in several types of culture for development and production purposes, with a directional and traction module that could be applied in other types of robots or autonomous vehicles. The drive and control circuits for the module motors have also been developed. The vehicle should be used for more advanced studies in the area of control, computer vision and artificial intelligence.